Step-up combination therapy with mizoribine for the treatment of patients with rheumatoid arthritis - Suzuki, Kimihiro (Clinical Rheumatology and Related Research, 2014)
Objective:To determine the efficacy and safety of step-up therapy with disease-modifying antirheumatic drugs (DMARDs), including mizoribine, in the treatment of patients with rheumatoid arthritis (RA). In addition,we aimed to identify the characteristics of patients who would benefit from step-up therapy with mizoribine. Methods:Step-up therapy with DMARDs including mizoribine was administered to patients with RA who visited our hospital between October 2009 and end of September 2013. Patients who received mizoribine for at least 6months were enrolled as subjects. Results: The mean age of the subjects was72. 3years; of these, 11patients (55％) were aged 70-79 years and 4 patients (20％) were aged ＞80years. Prior to the initiation of mizoribine treatment, most patients were treated with an average of 3.5 agents. The mean number of agents used for treating these patients was 4.6, among which mizoribine was added last during treatment in 6patients. The change in Disease Activity Score-28-C-reactive protein (DAS 28-CRP) scores after initiation of step-up therapy with mizoribine were as follows:initial medical examination, 2.97; initiation of mizoribine treatment, 2.82; and final evaluation, 2.21. A significant decrease in the DAS 28-CRP score was observed, as compared to the baseline score (p＝0.043). Adverse events were noted in 5 patients (25％), which included herpes zoster in 4patients, skin infection in 2 patients (toe paronychia and dermatitis, one in each patient), and acute exacerbation of chronic bronchitis in 1patient. All symptoms were resolved by drug withdrawal, or treatment with appropriate medication, and the step-up therapy could be resumed. Conclusion: We observed that step-up therapy with mizoribine has been shown to be a potentially useful treatment option for the treatment of RA patients having a complication and elderly patients who should be treated carefully.